Robust Ethylenedioxythiophene–Vinylene Oligomers from Fragile Thiophene–Vinylene Cores: Synthesis and Optical, Chemical and Electrochemical Properties of Multicharged Shapes. Issue 4 (19th November 2014) - Mayorga Burrezo, Paula; Pelado, Beatriz; Ponce Ortiz, Rocío; De la Cruz, Pilar; López Navarrete, Juan T.; Langa, Fernando; Casado, Juan
Abstract Oligomers of ethylendioxythiophene–vinylene have been prepared. Their optical, electrochemical and chemical properties have been studied in detail by absorption and emission spectroscopy as well as cyclic voltammetry, Raman techniques and spectroelectrochemistry complemented with quantum chemical calculations. A comparison with their non‐ethylendioxy and non‐vinylene parents has been done. The inclusion of the EDO plus the vinylene function generates more robust electronic ground states regarding the largely flexible thiophene–vinylene (n TV) oligomeric homologues. The redox features of the new compounds are also rich of oxidative processes arising as an interesting stabilising balance effect between the oxygen fragment in the EDO groups (mesomeric effect) and the linear π‐conjugated structure. The oxidised species have been characterised, which show the ability for the formation of mixed valence charge‐transfer complexes and π dimers of different oxidation states, in particular, in the electrochemical medium, resulting that the electrochemical response is accounted for a succession of aggregation and electron‐transfer steps. With this work, a full understanding of the optical and electronic properties of these new oligomers in the context of the oligomer approach has been proposed.